An Integrated Architecture for Processing Business Documents in Turkish - Adali, Serif; Sonmez, A. Coskun; Gokturk, Mehmet (SPRINGER-VERLAG BERLIN, 2009)
This paper covers the first research activity in the field of automatic processing of business documents in Turkish. In contrast to traditional information extraction systems which process input text as a linear sequence of words and locus on semantic aspects, proposed approach doesn't ignore document layout information and benefits hints provided by layout analysis. In addition, approach not only checks relations of entities across document for verifying its integrity, but also verifies extracted information against real word data (e.g. customer database). This rule-based approach uses a morphological analyzer for Turkish, a lexicon integrated domain ontology, a document layout analyzer, an extraction ontology and a template mining module. Based on extraction ontology, conceptual sentence analysis increases portability which requires only domain concepts when compared to information extraction systems that rely on large set of linguistic patterns.
Keywords: INFORMATION EXTRACTION; Computer Science